Investigation of sirtuin 1 polymorphisms in relation to the risk of colorectal cancer by molecular subtype - Hrzic, Rok (Sci Rep, 2020)
Sirtuin 1 (SIRT1), a histone deacetylase, is involved in maintenance of genetic stability, inflammation, immune response, metabolism (energy-sensing molecule) and colorectal tumorigenesis. We investigated SIRT1’s specific role in colorectal tumorigenesis by studying SIRT1 polymorphisms in relation to colorectal cancer (CRC) risk by microsatellite instability (MSI) and CpG island methylator phenotype (CIMP) status. The Netherlands Cohort study (NLCS) was initiated in 1986 and includes 120,852 participants in a case-cohort design. CRC tumour samples were available for incident cases between 1989 and 1993. Toenail deoxyribonucleic acid (DNA) was used for genotyping of two SIRT1 tagging variants (rs10997870 and rs12778366). Excluding the first 2.3 years of follow-up, subcohort members and CRC cases with no toenail DNA available and those with low sample call rates, and CRC cases with no tumour DNA available left 3478 subcohort members and 533 CRC cases. Cox regression was utilised to estimate hazard ratios (HRs) for MSI and CIMP positive and negative tumours by SIRT1 genotypes. The results were that the rs12778366 TC/CC versus TT genotype was inversely associated with MSI CRC (HR = 0.41, 95% confidence interval: 0.20, 0.88), while no association was found with the risk of an MSS tumour (TC/CC versus TT carriers: HR = 1.13, 95% CI: 0.89, 1.44). No significant associations were found between other SIRT1 genotypes and CRC subtypes. In conclusion, the results suggest a role for SIRT1 polymorphisms in colorectal tumorigenesis, particularly MSI CRC.